Strengthening Character Education through Digital Literacy in Elementary Schools: Challenges and Opportunities in So-ciety 5.0 Era - Iffah Zahrotul Khasanah; Salma Natha Erlinda; Nesya Nabila Az Zahra; Vikar Waruwu; Zulmi Roestika Rini (Proceeding International Collaborative Conference on Multidisciplinary Science, 2026)
The rapid convergence of digital technology and everyday life in the Society 5.0 era has reshaped how elementary school students learn, socialize, and build their character. While digital literacy equips young learners with the technical and cognitive skills needed to navigate digital environments, character education remains essential to ensure that technological fluency is balanced with ethical judgment, empathy, and social responsibility. This study examines the interconnection between digital literacy and character education for elementary school students, identifies the challenges faced by teachers and schools in integrating both competencies, and explores the opportunities that Society 5.0 offers for strengthening character formation through digital means. A qualitative narrative literature review method was employed, synthesizing findings from national and international peer-reviewed journal articles published between 2018 and 2025. The results indicate that digital literacy contributes positively to character strengthening when it is deliberately embedded in classroom pedagogy and supported by teacher competence, parental supervision, and school policy. However, challenges such as unequal digital access, teachers' limited digital pedagogical skills, and students' exposure to cyberbullying and misinformation continue to hinder effective implementation. The study concludes that strengthening character education through digital literacy requires a collaborative, human-centered approach involving teachers, families, and communities, consistent with the Society 5.0 vision of technology that serves human values.